Ectopic pregnancy: a comprehensive analysis of risk factors and management - Yadav, Dinesh Pal; Bhati, Indra; Bhati, Balgopal Singh (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Ectopic pregnancy is the most life threatening emergency in pregnancy leading to maternal death. Ectopic pregnancy jeopardizes the wish of attainment of motherhood also. Increase in incidence of pelvic inflammatory disease (PID), previous history of D and C and abortion, previous abdominal surgeries and use of assisted reproductive techniques are the various risk factors for ectopic pregnancy. The objective of this study was to assess the demographic profile, risk factors, clinical presentation and surgical management of ectopic pregnancy at a tertiary care centre. Methods: A prospective, longitudinal and observational study was conducted in the department of obstetrics and gynaecology, Umaid Hospital, Dr. SN Medical College, Jodhpur during a period of one year from October 2014 to September 2015. 80 cases of ectopic pregnancy admitted in the hospital were analyzed in terms of demographic profile, risk factors, clinical presentation, management, morbidity, mortality. Finally all collected material and data were analyzed statistically to draw various informative conclusions. Results: Most common age and parity affected by ectopic pregnancy were 21-30 years (63.75%) and para 1-3 (72.50%) respectively. No age and parity were immune to ectopic pregnancy. More than one clinical feature was present in most of the patients. Most common site of ectopic pregnancy was ampullary region (51.25%) of the tube. Salpingectomy was the most common surgical procedure performed (75%). Few patients had more than one complication. 29 cases had no complication. No maternal mortality occurred during this period. Around 50% women received blood transfusion. Conclusions: Ectopic pregnancy is a life-threatening condition occurring in women all over the world. As the incidence of ectopic pregnancy increases, ways and means have to be found to reduce the associated morbidity and mortality and to preserve future fertility.